Surviving the white space: perspectives on how middle-class Black men navigate cultural racism. Issue 14 (14th November 2021) - Hudson, Darrell; Sacks, Tina A.; Sewell, Whitney; Holland, Derek; Gordon, Jacob
ABSTRACT: Due to widespread, deeply entrenched racial residential segregation, public spaces in the United States are often overwhelmingly white. Middle-class Black Americans frequently work, live and recreate in predominantly white settings. Based on focus groups with Black men in St. Louis, we found that middle-class Black men often (1) survive the white space; (2) were hyper-visible, or in the spotlight; and (3) were vigilant. Study findings illuminate how racism continues to affect racial minorities who are not poor but who are nonetheless impacted by racism. Second, the findings suggest that by virtue of their class status, middle-class Black men are frequently isolated at work, school, or in their neighbourhoods. Based on these findings, we suggest more robust measures of discrimination to better capture the constant negotiation of cultural racism as well as the toll these negotiations exact on the overall well-being of Black men.